Symptomatic carotid atherosclerotic disease: correlations between plaque composition and ipsilateral stroke risk - Howard, Dominic PJ (Stroke, 2014)
BACKGROUND AND PURPOSE: For symptomatic patients with carotid artery stenosis the risk-benefit for surgical intervention may vary among patient groups. Various modalities of plaque imaging have been promoted as potential tools for additional risk stratification, particularly in patients with moderate stenosis. However, it remains uncertain to what extent carotid plaque components predict risk of future ipsilateral ischaemic stroke. METHODS: In two large atherosclerotic carotid plaque biobank studies, we related histological characteristics of 1640 carotid plaques with a validated risk model for the prediction of individual 1- and 5-year stroke risk. RESULTS: No significant heterogeneity between the studies was found. Predicted 5-year stroke risk (top versus bottom quartile) was related to plaque thrombus (OR=1.42, 95%CI 1.11-1.89, p=0.02), fibrous content (0.65, 0.49-0.87, p=0.004), macrophage infiltration (1.41, 1.05-1.90, p=0.02), high micro-vessel density (1.49, 1.05-2.11, p=0.03), and overall plaque instability (1.40, 1.05-1.87,p=0.02). This association was not observed for cap thickness, calcification, intra-plaque haemorrhage, or lymphocyte infiltration. Plaques removed within 30-days of most recent symptomatic event were most strongly correlated with predicted stroke risk. CONCLUSIONS: Features of ‘the vulnerable carotid plaque’ including plaque thrombus, low fibrous content, macrophage infiltration and microvessel density correlate with predicted stroke risk. This study provides a basis for plaque imaging studies focused on stroke risk stratification.